In vitro validation of a method for neonatal urine collection and analysis. Issue 1 (26th June 2019) - Ritchie, Darren; Broadbent, Roland; Medlicott, Natalie; Reith, David M
Abstract : Objective: Urine collection and analysis is important for diagnosis, monitoring of clinical progress, and research in neonates. This study aims to validate a novel methodology for neonatal urine collection, which combines the convenience of cotton ball collection with accurate timing via a urine continence monitor. Design: Laboratory model using a combined cotton ball and urinary incontinence monitor method with and without the presence of an impermeable membrane to prevent desiccation. Main outcome measures: Accuracy, bias and precision in measurement of urine volume, electrolytes (sodium, potassium, chloride), creatinine and gentamicin. Changes in analyte concentration over time, and evaporative loss of water, were tested using analysis of variance. The effects of time, temperature and humidity were explored using multivariate analysis of variance. Results: With the use of an impermeable membrane, sodium concentration increased from a mean (SD) of 3.57% (0.68) at 1 min to 5.03% (0.74) at 120 min. There was no significant change in potassium, chloride or creatinine concentrations. Gentamicin concentration decreased by a mean (SD) of 9.05% (1.37) by 30 min. Multivariate analysis found that absolute change in weight, sodium and chloride were only dependent on duration. Gentamicin concentration was affected by duration, humidity and temperature. Relative evaporative loss was minimal at −0.58% (0.31), and the urinary continence monitor was 100% successful at detecting urination for all time points. Conclusions: This novel methodology provides a standardisable and practical method to collect small volumes of neonatal urine for accurate measurement of both urine output and analyte concentrations.